Simple Booking Training For Batik Jonegoro Wirausahaan Women In Bojonegoro District - Nur Laily; Yudi Sidharta; Achmad Djuraidi (Kontribusia : Research Dissemination for Community Development, 2020)
The purpose of Community Service Activities Simple Bookkeeping Training for Women entrepreneur batik Jonegoro can make simple bookkeeping so that it is orderly in carrying out its financial records so that it can be measured the expenditure, income, and profits obtained and can know the progress of the business. The method used by training. The results obtained from this training activity can increase entrepreneurial knowledge and skills in making simple bookkeeping to increase motivation in work. The conclusion is simple bookkeeping training received a positive response and businesses get knowledge and skills about new insights in running their business through simple financial bookkeeping/recording that is easy to apply.